Merdeka Belajar Dalam Pandangan Alqur’an Hadis - Yustin Kamaru; Kasim Yahiji; Rahmin Thalib Husain; Ilyas Daud (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Merdeka belajar is a concept of education that gives learners the freedom to learn according to their interests, talents, and abilities. This concept is in line with the Islamic view that learning is a duty and a need for every human being. In the Qur'an, the concept of merdeka belajar can be found in several verses, such as QS Al-Alaq verse 1-5 which commands humans to read and learn. This verse shows that learning is important and must be done by every human being. In the hadith, the concept of merdeka belajar can also be found. For example, in a hadith narrated by Al-Bukhari, the Prophet Muhammad PBUH said,